Ectopic expression of the PISTILLATA homologous MdPI inhibits fruit tissue growth and changes fruit shape in apple. (14th April 2018) - Yao, Jia‐Long; Xu, Juan; Tomes, Sumathi; Cui, Wei; Luo, Zhiwei; Deng, Cecilia; Ireland, Hilary S.; Schaffer, Robert J.; Gleave, Andrew P.
Abstract: Fruit shape represents a key trait that consumers use to identify and select preferred cultivars, and although the manipulation of this trait is an opportunity to create novel, differentiated products, the molecular mechanisms regulating fruit shape are poorly understood in tree fruits. In this study, we have shown that ectopic expression of Malus domestica PISTILLATA (MdPI), the apple ortholog of the floral organ identity gene PISTILLATA (PI), regulates apple fruit tissue growth and shape. MdPI is a single‐copy gene, and its expression is high during flower development but barely detectable soon after pollination. Transgenic apple plants with ectopic expression of MdPI produced flowers with white sepals and a conversion of sepals to petals. Interestingly, these plants produced distinctly flattened fruit as a consequence of reduced cell growth at the basipetal position of the fruit. These altered sepal and fruit phenotypes have not been observed in studies using Arabidopsis . This study using apple has advanced our understanding of PI functions outside the control of petal and stamen identity and provided molecular genetic information useful for manipulating fruit tissue growth and fruit shape.